Settlement of Waqf Disputes by Deliberation to Reach Consensus - Riza, Faisal; Zainuddin, Zainuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Waqf functions to realize the potential and economic benefits of waqf property for the benefit of worship and to promote public welfare. The use of the waqf property needs to be developed in accordance with sharia principles, but in fact, there are still problems that the waqf property is not in accordance with its function. Waqf assets are requested or taken back by the wakif or wakif heirs, or vice versa, the waqf assets are controlled from generation to generation by nazhir whose use deviates from the waqf contract, is not responsible for his obligations to maintain the waqf property, neglect or transfer it. To third parties in an unlawful manner. This study will explore and examine the process of resolving disputes over waqf property. Is the settlement process by deliberation better than proceeding through the courts? Because the issue of waqf has been regulated in Law Number 41 of 2004 concerning Waqf. The law regulates how to waqf property, develop waqf assets and how to resolve waqf disputes through deliberation to reach consensus. It is better if the dispute over waqf property is first resolved by deliberation to reach consensus. The legal basis for deliberative settlement is regulated in Article 62 of Law Number 41 of 2004 concerning Waqf, but the detailed process is not regulated so that it is almost equated with the mediation process so that the disputing parties prefer to go through the courts, even though the deliberative settlement process is very good.